Avaliação da atenção pré-natal em Municípios da 15ª Regional de Saúde - PR - Vieira, Viviane Cazetta de Lima (2011)
The prenatal includes a set of activities that seeks the promotion of the health of pregnant women and the fetus and the establishment of appropriate actions to prevention, diagnosis and the clinical handling of obstetric problems that may happen. The objective of this study was to evaluate the prenatal care in municipalities belonging to the 15th Regional of Health - PR. The population sample was intentionally selected, consisted by 136 postpartum women, who accomplished prenatal care accompaniment exclusively in the public net of the selected municipalities. A semi-structured questionnaire for interview was used with the postpartum women, data for research from the pregnant woman card and data collection in the medical records of UBS where the prenatal care was held. The data obtained were identified by municipalities, grouped and discussed by population stratum divided like this: smaller municipalities than 20,000 inhabitants, between 20,000 and 50,000 inhabitants, and larger than 50,000 inhabitants. There were predominance of postpartum women in the age group between 21 and 30 years, in the three population strata. In municipalities with population less than 20,000 inhabitants the postpartum women presented the highest level of education (87.4%) with high school, as well as the highest percentage (71.4%) of women with an occupation outside the home. Regarding the knowledge about contraceptive methods the postpartum women residing in the municipalities with larger population than 50,000 were the ones who informed to know a larger number of methods (62.7% reported knowing more than three methods). The average weight of the newborns in the three population strata was considered adequate and 86% of them the index apgar was greater than seven. The nurse showed little inserted in the care of mother, mainly in municipalities with larger population than 50,000 inhabitants, where 8% of the postpartum women reported being assisted by doctors and nurses and 2.2% were only assisted by nurses. A smaller number of exams of the prenatal routine was verified, registered in medical records, in the municipalities with population less than 20,000 inhabitants (28.55%) when compared to municipalities between 20,000 and 50,000 inhabitants (74.5%) and more than 50,000 inhabitants (52.8%). The Community Health Agents (CHA) was the most remembered professional within the Family Health Strategy (FHS), but only 37% of the postpartum women reported having received home visits during pregnancy. The prenatal care was considered "good" in the opinion of the postpartum women. The ones who considered the attendance great resided in municipalities with less than 50,000 inhabitants. Differences were observed in the prenatal care in relation to population strata, demonstrating the need of such studies in municipalities with different population sizes.